2006
DOI: 10.1007/s00402-006-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of hollow cylinder based spinal implants in normal and osteoporotic vertebrae: a sheep study

Abstract: The high number of perforations, filled with intact trabeculae, indicates an adequate fixation; bridging trabeculae between adjacent endplates and tricortical iliac struts in all vertebrae indicates that the anchorage is adequate to promote fusion in this animal model, even in the osteoporotic sheep.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Sheep have been widely used as an animal model in orthopedic research (16), and as osteoporosis models in numerous studies (17)(18)(19). However, the time required to establish an accurate osteoporosis model remains inconsistent between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep have been widely used as an animal model in orthopedic research (16), and as osteoporosis models in numerous studies (17)(18)(19). However, the time required to establish an accurate osteoporosis model remains inconsistent between studies.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Results of one biomechanical animal study have demonstrated an association of mean tissue density and compressive strength of calf spines with a young healthy human spine. [25] Hence, in experimental study, animal spines are used as a substitute for human cadaveric specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the osteoporosis related bone loss and instrumentation of osteoporotic vertebra is important in understanding bone mechanics and development of new and improved implant designs [8,11]. Access to consistent and high quality human cadaveric tissue is limited.…”
Section: Introductionmentioning
confidence: 99%